Initiating insulin as part of the Treating To Target in Type 2 Diabetes (4-T) trial: an interview study of patients' and health professionals' experiences. - Jenkins, N; Hallowell, N; Farmer, A; Holman, R; Lawton, J (2010)
OBJECTIVE: To explore patients' and health professionals' experiences of initiating insulin as part of the Treating To Target in Type 2 Diabetes (4-T) randomized controlled trial. RESEARCH DESIGN AND METHODS: Interviews were conducted with 45 trial participants and 21 health professionals and thematically analyzed. RESULTS: Patients were generally psychologically insulin receptive when approached to participate in the 4-T trial. Their receptiveness arose largely from their personal experiences observing intensifying prior treatments and deteriorating blood glucose control over time, which led them to engage with and accept the idea that their diabetes was progressive. Health professionals also fostered receptiveness by drawing on their clinical experience to manage patients' anxieties about initiating insulin. CONCLUSIONS: Previous studies may have overemphasized the problem of psychological insulin resistance and overlooked factors and treatment experiences that may promote insulin receptiveness among type 2 patients.